2010
DOI: 10.1111/j.1939-1676.2010.0645.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Brain Injury in Foals with Hypoxic‐Ischemic Encephalopathy

Abstract: Background: Neonatal hypoxic-ischemic encephalopathy (NHIE) is a disease affecting newborn foals for which there is no antemortem diagnostic test.Hypothesis: Ubiquitin C-terminal hydrolase 1 (UCHL1) and the phosphorylated axonal forms of neurofilament H (pNF-H) are markers of brain injury in foals with NHIE.Animals: Thirty-three foals with a clinical diagnosis consistent with NHIE and 17 healthy foals. Methods: Retrospective study. Concentrations of UCHL1 and pNF-H in plasma were measured by ELISA. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
3
34
0
1
Order By: Relevance
“…A recent article investigating biomarkers of brain injury in foals with HIE described the pathologic findings of 3 foals that had performed histopathology. There was neuronal necrosis of the gray matter of the cerebral cortex, caudate nuclei, thalamus, hippocampus, cerebellar cortex, and medulla oblongata, which was consistent with a diagnosis of hypoxic ischemic brain injury …”
Section: Neuropathologysupporting
confidence: 59%
“…A recent article investigating biomarkers of brain injury in foals with HIE described the pathologic findings of 3 foals that had performed histopathology. There was neuronal necrosis of the gray matter of the cerebral cortex, caudate nuclei, thalamus, hippocampus, cerebellar cortex, and medulla oblongata, which was consistent with a diagnosis of hypoxic ischemic brain injury …”
Section: Neuropathologysupporting
confidence: 59%
“…A second generation pNF-H assay, using a novel monoclonal pNF-H capture antibody screened originally by ability to capture pNF-H from concentrated protein solutions, has also been described and is marketed by EnCor Biotechnology (M α -pNF-H ELISA) [39]. These ELISA methods have been used to measure pNF-H in serum in several neurological conditions including aneurysmal subarachnoid haemorrhage [40], amyotrophic lateral sclerosis [39], Leber's hereditary optic neuropathy [41], and neonatal hypoxic-ischemic encephalopathy [42, 43], but no publication has as yet described the use of this assay on plasma or serum samples from MS patients. …”
Section: Neurofilament Protein Subunits As Blood Biomarkers Of Axomentioning
confidence: 99%
“…Recent studies have shown that neurobiomarkers [6,7,8,9] may be useful indicators of neural tissue compromise in foals.…”
Section: Introductionmentioning
confidence: 99%